UJI KETAHANAN 10 TANAMAN PADI VARIETAS LOKAL BANTEN TERHADAP PENYAKIT HAWAR DAUN BAKTERI (Xanthomonas oryzae pv. oryzae) PADA FASE PERSEMAIAN - Sunariah Fany Ali; Dewi Hastuti; Andree Saylendra (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2012)
Bacterial leaf blight disease is an economically important disease for the growth of rice plants. The research was aimed to know the most resistant varieties to bacterial (Xanthomonas oryzae pv. oryzae) in seedling phase. The research was conducted May up to Juli 2012 at Green House Livestock, Agriculture and Horticulture UPTD Serang city. The research used a Randomized Completely Blok Design (RCBD) with one factor, each one tray planted 3 varieties. Test varieties were planted in the middle, on the right was susceptible variety (IR-64) and to the left of the comparison resistant variety (Conde). Each variety was planted 10 seeds, so there were 30 rice stalks. There were 10 trays experiment, with 3 replications. Overall there were 30 trays trial. Results of research showed that from 10 varieties had tested, levels of resistance to bacterial leaf blight disease (BLB) in seedling phase were: (1) Waler 17,56 %, (2) Tambleg 18,46 %, (3) Kewal Bulu Hideng 20, 43 %, (4) Gadog 20,84 %, (5) Jaketra 21,58 %, (6) Kewal Cere 23,65 %, (7) Ketan Laleur 25,80 %, (8) Jalawara Hawara 26,29 %, (9) Ketan Solo 29,20 %, (10) Kewal Gudril 29,93 %. The fastest BLB incubation period was local variety of Kewal Gudril within 4-5 days.Key words : Local Varieties of Banten, Bacterial Leaf Blight, Xanthomonas oryzae pv. oryzae, Resistance and Disease Intensity.